STRATEGI SENIMAN PUCKMUDE DALAM MEMPERTAHANKAN EKSISTENSI TERHADAP PERKEMBANGAN MUSIK DI KOTA PONTIANAK - Nanda, Gilang Ocktantrio; Istiandini, Winda; Muniir, Asfar (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2020)
Â AbstractThis research aims to describe the existence, factors that influenced, and efforts to maintain the existence of Puckmude music artists. The method that used is descriptive method. Describing the existence of Puckmude was obtained through observation and interviews with interviewees, and documenting Puckmude's activities.The results showed that Puckmude still exists today (2018). The Factors that affecting the existence of them are financial, lack of appreciation, the globalization, and lack of assistance from the local government.Efforts to maintain existence by growing regeneration for the young generation, increasing income, assistance from the government and utilize the internet sites as promotional media. The results of this research are expected to be a reference for further research on independent music.Â Keywords: Puckmude , Existence, Independent Music